Pre-Loaded Fenestrated Thoracic Endografts for Distal Aortic Arch Pathologies: Multicentre Retrospective Analysis of Short and Mid Term Outcomes. (December 2021) - Tsilimparis, Nikolaos; Prendes, Carlota F.; Rouhani, Guido; Adam, Donald; Dias, Nuno; Stana, Jan; Rohlffs, Fiona; Mani, Kevin; Wanhainen, Anders; Kölbel, Tilo
Abstract : Objective: To determine short and midterm outcomes of a pre-loaded fenestrated thoracic endograft (f-TEVAR) for exclusion of distal aortic arch pathologies. Methods: This was a multicentre, retrospective study including consecutive patients from six experienced European vascular centres undergoing f-TEVAR for distal arch pathologies. Primary endpoints included peri-operative mortality and peri-operative stroke and/or spinal cord ischaemia rates. Secondary outcomes were technical success and mid to late events, including death and re-interventions. Statistical analysis was performed with SPSS 26. Mid to late term events were calculated using Kaplan–Meier survival analysis. Results: One hundred and eight patients were included (mean age 68 ± 11 years, 70% men). A total of 38% ( n = 42) had a prior history of aortic dissection, and 24% ( n = 26) prior aortic surgery. The mean aneurysm diameter was 59 ± 12 mm and the most frequent indication for treatment was post-dissection aneurysms ( n = 42, 39%). Technical success was 99% ( n = 107) despite intra-operative wire entanglement occurring in 29% ( n = 31). The 30 day mortality rate was 3.7% ( n = 4), with a 5.6% major stroke incidence ( n = 6) and 3.7% ( n = 4) spinal cord ischaemia rate. Three cases of retrograde dissection occurred (two of which were fatal), all in post-type B dissecting aneurysm patients without prior aortic surgery (three of 19, 15.8%). Median follow up was 12 months (range, 1 – 26). Endoleaks were documented during follow up, with 3.5% type Ia (4/104) and 2.9% type Ib (3/104) as a result of persistent false lumen perfusion. The one, two, and three year survivals and freedom from re-intervention rates were 93.2% and 92.1%, 89.1% and 86.3%, and 84.4% and 73%, respectively. Conclusion: This multicentre study shows that treatment of the distal aortic arch by f-TEVAR is feasible, with promising 30 day mortality, stroke, and spinal cord ischaemia rates.